2009
DOI: 10.1128/jcm.01563-08
|View full text |Cite
|
Sign up to set email alerts
|

Unreliability of Results of PCR Detection of Helicobacter pylori in Clinical or Environmental Samples

Abstract: The aim of this study was to compare published Helicobacter pylori primer pairs for their ability to reliably detect H. pylori in gastric biopsy specimens and salivary samples. Detection limits of the 26 PCR primer pairs previously described for detection of H. pylori DNA in clinical samples were determined. Sensitivity and specificity were determined using primers with detection limits of <100 CFU/ml using 50 H. pylori-positive and -negative (by concordance by culture and histology) coded gastric biopsy speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 55 publications
1
76
0
Order By: Relevance
“…Other species of bacteria that secrete urease in the plaque, such as Streptococci, Actinomyces or Haemophilus spp, can cause false positives. 18,19 The research team of Silva et al demonstrated a correlation between the colonization of supragingival plaque and oral health parameters -specifically, between the percentage of the surface covered with dental plaque and the bleeding rates of periodontal pockets. 16 Patients with higher values of these 2 indicators were likely to report the presence of H. pylori in their oral cavities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other species of bacteria that secrete urease in the plaque, such as Streptococci, Actinomyces or Haemophilus spp, can cause false positives. 18,19 The research team of Silva et al demonstrated a correlation between the colonization of supragingival plaque and oral health parameters -specifically, between the percentage of the surface covered with dental plaque and the bleeding rates of periodontal pockets. 16 Patients with higher values of these 2 indicators were likely to report the presence of H. pylori in their oral cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Dental plaque has been called "a reservoir for genotypes", where horizontal gene transfer can take place between the bacteria that reside in the biofilm. 17,18 The genotypic variability of this bacteria manifests itself in the presence of point mutations and changes in the gene sequence. This may lead to both false positive and false negative results if the PCR test is limited to determining a single gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of test not only diagnoses the amount of damage in the stomach but also allows the clinician to directly sample the tissue to test it for the presence of the H. pylori organism. Noninvasive tests can identify H. pylori in a sample, but do not reveal the amount of tissue damage (Fleming et al 2009;Sugimoto et al 2009). …”
Section: Diagnosis Of H Pylori Infectionmentioning
confidence: 99%
“…Reprinted with permission from Deretsky (2015) et al 2000; Monteiro et al 2001b). However, the specificity and sensitivity of the diagnosis varies, according to different sample preparations and various laboratory conditions (Sugimoto et al 2009). Monoplex, multiplex, and nested PCR methods are useful for specially identifying H. pylori in biological samples.…”
Section: Invasive Testsmentioning
confidence: 99%